Microbial degradation of polyfluoroalkyl chemicals in the environment: A review - Liu, Jinxia; Mejia Avendaño, Sandra (Environment international, 2013)
Polyfluoroalkyl chemicals containing perfluoroalkyl moieties have been widely used in numerous industrial and commercial applications. Many polyfluoroalkyl chemicals are potential perfluoroalkyl acid (PFAA) precursors. When they are released to the environment, abiotic and microbial degradation of non-fluorinated functionalities, polyfluoroalkyl and perfluoroalkyl moieties can result in perfluoroalkyl carboxylic (PFCAs) and sulfonic acids (PFSAs), such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS). These highly persistent and ubiquitously detected PFAAs are the subjects of many regulations and actions due to their toxic profiles. In order to confidently evaluate the environmental fate and effects of these precursors and their links to PFSAs and PFCAs, we present the review into the environmental biodegradability studies carried out with microbial culture, activated sludge, soil and sediment in the past decade. First, we propose that the knowledge gap caused by the lack of direct detection of precursor chemicals in environmental samples can be bridged by laboratory investigations of important precursors such as fluorotelomer-based compounds and perfluoroalkane sulfonamido derivatives. Then we evaluate the experimental setups and methodologies, sampling and sample preparation methods, and analytical techniques that have been successfully applied. Third, we provide the most updated knowledge on quantitative and qualitative relationships between precursors and PFSAs or PFCAs, microbial degradation pathways, half-lives of precursors, defluorination potential, and novel degradation intermediates and products. In the end, we identify knowledge gaps and suggest research directions with regard to future biodegradation studies, environmental monitoring and ecotoxicological assessment of perfluoroalkyl and polyfluoroalkyl chemicals.